Brand relevance : making competitors irrelevant - Aaker, David A. (San Francisco, CA : Jossey-Bass, 2011)
'Substantial market trends and transformational innovations are creating markets and making others irrelevant. The result is a major threat for nearly every business and a significant opportunity for a few. This book will be the first marketing strategy book to develop and leverage the concept of brand relevance. To remain relevant, a firm can create a new category or subcategory-- such as iPod, Cirque du Soleil, and eBay did-- where competitors are eliminated. Or a firm can redefine an existing category or subcategory by creating or elevating an offering feature or characteristic--as Prius created a subcategory defined by gas mileage and technology, or Westin did with its Heavenly Bed. In either case, a firm can create or own a new business arena or submarket in which some or all competitors are not relevant. Instead of being the best, the goal is to be the only--making competitors irrelevant'--
Winning the brand relevance battle -- Understanding brand relevance: categorizing, framing, consideration, and measurement -- Changing the retail landscape -- Market dynamics in the automobile industry -- The food industry adapts -- Finding new concepts -- Evaluation -- Defining and managing the category or subcategory -- Creating barriers: sustaining the differentiation -- Gaining and maintaining relevance in the face of market dynamics -- The innovative organization.
Includes bibliographical references and index.
Keywords: Brand name products; Branding (Marketing); Technological innovations